EFISIENSI PEMASARAN KOMODITAS MANGGIS DI KABUPETAN TASIKMALAYA - Ulpah Jakiyah; Syahrul Ganda Sukmaya (Universitas Galuh Ciamis, 2020)
Marketing mangosteen in Kabupaten Tasikmalaya has reached around the country one of them China. Exports mangosteen carried out by several distributors mangosteen who was in the district of tasikmalaya one of them PT Java Fresh. The selling price mangosteen for export reached rp 30.000 / kg while the price level farmers around rp 3500-rp 5000 / kg. So that the purpose of this research is to measure the efficiency mangosteen marketing for export activity in the district. tasikmalayaBased on the research results obtained that export marketing outlets there are two channels that come with the quality of super ( sp ).A channel 1 mangosteen sp quality from the farmers be channeled to merchants ( village middleman ) with the percentage 70 percent of the harvest.A channel 2 farmers sell to trader sells directly to the exporters. sub districtThe added value to every channel there are only on an activity of cleaning and sorting. Margins marketing the highest is exporters with distribution margin of 56.6 percent of the channel 1 and 60 percent of the channel 2. While the ratio of gains against the most are the intermediary village. This is the cost is relatively small in comparison to other institusions marketing. Based on price and, operational efficiency marketing mangosteen efficient done because advantage or the differences in price greater than the cost by each institution marketing.